Menciptakan Minat Beli Produk Scarlett: Analisis Kontribusi Influencer, Word Of Mouth dan Brand Image - Astuti, Puji; Qoiriyah, Mila; Rojuaniah, Rojuaniah; Havidz, Ikramina Larasati Hazrati; Wati, Diana Fajar (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this research is to analyze the contribution of influencers, word of mouth, and brand image in creating interest in buying a product. By using data collection techniques in this research, distributing questionnaires online to a sample of respondents who have been selected based on purposive sampling, namely Tasya Farasya followers who use Scarlett Whitening products. This research is quantitative research with the SEM (Structural Equation Modeling) method using SmartPLS and Lisrel software. The results of this research obtained several findings, namely Perceived Information Value from Influencers has a positive effect on Perceived Influence, Perceived Influence by Followers has a positive effect on Perceived WOM Communication, Perceived Influence by Followers has a positive effect on Intention to Purchase Recommended Brand, Perceived WOM Communication has a positive effect on Brand Image , Emotional Attachment with Influencers has a positive effect on Perceived Influence, Perceived WOM Communication has a positive effect on Intention to Purchase Recommended Brand, Brand Image has a positive effect on Intention to Purchase Recommended Brand